The birds of Reserva Extrativista Chico Mendes, South Acre, Brazil - Mestre, Luiz Augusto Macedo; Thom, Gregory; Cochrane, Mark Alan; Barlow, Jos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
This paper describes the avifauna sampled at Reserva Extrativista Chico Mendes, Acre, Brazil, during October and November, 2008. We recorded 344 bird species of 17 orders and 57 families through point counts, mist-nets and general observations. The most prevalent families were Tyrannidae, Thamnophilidae and Thraupidae with 53, 36 and 22 species, respectively. We recorded some range restricted, little know, and habitat specialists birds exemplified by Crypturellus atrocapillus, C. strigulosus, Primolius couloni, Aulacorhynchus prasinus, Drymophila devillei, Simoxenops ucayalae, Cnipodectes superrufus, Hemitriccus flammulatus, Percnostola lophotes, Xiphorhynchus chunchotambo, and Conioptilon mcilhennyi. Although we surveyed only during the dry season, the rarefaction curves indicate a satisfactory sampling effort. The data show that the Chico Mendes reserve holds a unique Amazonian bird community, which is influenced by the presence of bamboo and second growth vegetation. The results of this paper reinforce the biological importance of the RESEX and highlight the need for more inventories and bird studies at this isolated and little known region of the Brazilian Amazon.
Keywords: Aves; Brazil; Southeast Acre; Southwest Amazon; Reserva Extrativista Chico Mendes